Essays on price theory and industrial organization - Bain, Joe Staten (Boston : Little, Brown, 1972)
This book includes applying economic analysis to empirical data the origination and elaboration on related theories.
MF22/01/2019
Loans
Keywords: Prices; Industrial organization